2012
DOI: 10.1111/j.1365-2745.2012.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and productivity‐mediated indirect effects of fertilization, mowing and grazing on grassland species richness

Abstract: Summary1. Recent declines in biodiversity have given new urgency to questions about the relationship between land-use change, biodiversity and ecosystem processes. Despite the existence of a large body of research on the effects of land use on species richness, it is unclear whether the effects of land use on species richness are principally direct or indirect, mediated by concomitant changes in ecosystem processes. Therefore, we compared the direct effects of land use (fertilization, mowing and grazing) on sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
228
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(259 citation statements)
references
References 49 publications
26
228
5
Order By: Relevance
“…Mowing found to decrease the abundance of disturbance sensitive species, while increased the disturbance-tolerant ruderal species by frequent destruction of above-ground plant organs (Socher et al, 2012). Enrichment of species or recovery after mowing might be due to enhanced seedling germination by the removal of litter and above-ground biomass, which creates gaps that act as suitable micro-sites for the establishment of small-seeded species (Socher et al, 2012). The species richness could change even during a short period of three years of mowing (once per year), however with unfavourable effects on the original dry grassland community (Jantunen, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mowing found to decrease the abundance of disturbance sensitive species, while increased the disturbance-tolerant ruderal species by frequent destruction of above-ground plant organs (Socher et al, 2012). Enrichment of species or recovery after mowing might be due to enhanced seedling germination by the removal of litter and above-ground biomass, which creates gaps that act as suitable micro-sites for the establishment of small-seeded species (Socher et al, 2012). The species richness could change even during a short period of three years of mowing (once per year), however with unfavourable effects on the original dry grassland community (Jantunen, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, grazing was found to increase (due to light grazing of cattle, Fritch et al, 2011) or decrease (due to overgrazing by horses, Penksza, 2005) the species richness compared to the mowing treatment (Fritch et al, 2011, Penksza, 2005. Mowing found to decrease the abundance of disturbance sensitive species, while increased the disturbance-tolerant ruderal species by frequent destruction of above-ground plant organs (Socher et al, 2012). Enrichment of species or recovery after mowing might be due to enhanced seedling germination by the removal of litter and above-ground biomass, which creates gaps that act as suitable micro-sites for the establishment of small-seeded species (Socher et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have already demonstrated the negative effects of fertilization on species richness Stewart and Pullin, 2008;Zechmeister et al, 2003). Recently, a study by Socher et al (2012) conducted in the same study regions has shown a loss of 19 % of the total number of vascular plant species on a grassland site with an annual fertilization input of 35 kg of N per hectare. Given the limited amount of grazed and mowed sites in our dataset, we did not find any significant effect of these management practices on root C age.…”
Section: Root 14 C Age In Grassland Ecosystemsmentioning
confidence: 98%